Proteomic analysis of lysine acetylation provides strong evidence for involvement of acetylated proteins in plant meiosis and tapetum function. (15th December 2017) - Li, Xiaojing; Ye, Juanying; Ma, Hong; Lu, Pingli
Summary: Protein lysine acetylation (KAC) is a dynamic and reversible post‐translational modification that has important biological roles in many organisms. Although KAC has been shown to affect reproductive development and meiosis in yeast and animals, similar studies are largely lacking in flowering plants, especially proteome‐scale investigations for particular reproductive stages. Here, we report results from a proteomic investigation to detect the KAC status of the developing rice anthers near the time of meiosis (RAM), providing strong biochemical evidence for roles of many KAC‐affected proteins during anther development and meiosis in rice. We identified a total of 1354 KAC sites in 676 proteins. Among these, 421 acetylated proteins with 629 KAC sites are novel, greatly enriching our knowledge on KAC in flowering plants. Gene Ontology enrichment analysis showed chromatin silencing, protein folding, fatty acid biosynthetic process and response to stress to be over‐represented. In addition, certain potentially specific KAC motifs in RAM were detected. Importantly, 357 rice meiocyte proteins were acetylated; and four proteins genetically identified to be important for rice tapetum and pollen development were acetylated on 14 KAC sites in total. Furthermore, 47 putative secretory proteins were detected to exhibit acetylated status in RAM. Moreover, by comparing our lysine acetylome with the RAM phosphoproteome we obtained previously, we proposed a correlation between KAC and phosphorylation as a potential modulatory mechanism in rice RAM. This study provides the first global survey of KAC in plant reproductive development, making a promising starting point for further functional analysis of KAC during rice anther development and meiosis. Significance Statement: Using nano ultra‐high‐pressure liquid chromatography–tandem mass spectrometry‐based proteomics we identified 676 lysine acetylated proteins with 1354 lysine acetylated sites in developing rice anthers (around the time of meiosis), revealing multiple biochemical and genetic pathways regulated by lysine acetylation, including a number of proteins in meiosis. These data provide a community resource with information on the abundance and lysine acetylation status of thousands of rice proteins in developing anthers, potentially greatly accelerating studies to elucidate molecular mechanisms of rice anther development and meiosis.